Pengaruh Strategi Pembelajaran DRTA (Directed Reading Thinking Activity) Terhadap Kemampuan Berfikir Kritis Bahasa Indonesia Siswa Kelas IV MI Hidayatus Shibyan Talun Cirebon - Millatul Fitriyah; Syibli Maufur; Idah Faridah Laily (Journal of Humanities, Social Sciences, and Education, 2025)
This study aims to (1) describe the implementation of the DRTA strategy in Indonesian language learning, (2) measure students' critical thinking skills before and after the implementation of the DRTA strategy, and (3) analyze the effect of the DRTA strategy on improving students' critical thinking skills. The formulation of the problem is the main basis in designing and implementing research with a focus on improving Indonesian language learning outcomes through effective and innovative learning strategies. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research subjects consisted of two classes, namely the experimental class and the control class. Data collection techniques were carried out through test instruments (pretest and posttest) and observation sheets. Data analysis was carried out using t-tests and N-Gain calculations to measure the effectiveness of the strategies implemented. The results of the study showed that the implementation of the DRTA strategy had a significant effect on improving students' critical thinking skills. This was proven by the results of the t-test with a significance value of 0.000 < 0.05, which indicated a significant difference between the experimental group and the control group. The N-Gain value obtained was 0.73 (high category) in the experimental class, while the control class only showed an increase of 0.51 (moderate category). Thus, the DRTA strategy has proven effective in improving students' critical thinking skills in Indonesian language learning. This strategy is able to create interactive and reflective learning, as well as train students to think logically, analyze information in depth, and draw conclusions based on existing evidence. Therefore, the DRTA strategy is recommended as an alternative learning approach that is relevant to be implemented in elementary schools to support the achievement of 21st-century skills.